An EXPLORATORY STUDY OF AIRPORT TRAVEL RETAIL SERVICE QUALITY AND ITS IMPACT ON AIRPORT REVENUES - Adi Nugroho; Bayu Arsan (FEB-UP Press, 2021)
As one of business entity engaged in airport services, Bali Airport is demanded to increase aeronautical and non-aeronautical revenue stream and also its service level. Where the non- aeronautical revenue produced from concessionaire activity in the airport terminal needs to have the right strategy.This study aims to investigate key atributes of the Service Quality of Travel Retail and analyze the influence of the Service Quality of Travel Retail on Non-Aeronautical Revenue. By using SmartPLS 3.0, the results of research showed that there was a low influence of the Service Quality of Travel Retail on Revenue performance.The research method used was quantitative design by distributing questionnaires to 160 respondents of Bali Airport passengers. The analysis process used was descriptive and validation by using SEM Partial Least Square (PLS) method Keywords :Service quality of travel retail, Bali Airport, Non-Aeronautical Revenue, revenue performance